Post-stroke pathway analysis and link with one year sequelae in a French cohort of stroke patients: the PAPASePA protocol study - S. Broussy; F. Rouanet; E. Lesaine; S. Domecq; M. Kret; M. Maugeais; F. Aly; P. Dehail; A. Bénard; J. Wittwer; R. Salamon; I. Sibon; et al. (BMC, 2019)
Abstract Background Stroke is a health problem with serious consequences, both in terms of mortality, and after-effects affecting patient quality of life. Stroke requires both urgent and chronic management involving the entire health care system. Although large variability in the management of stroke patients have been noticed, knowledge of the diversity and the scalability of post-stroke pathways, whether it is the care pathway or the life pathway, is currently not sufficient. Moreover the link between post-stroke pathways and patients sequelae have not been yet clearly defined. All this information would be useful to better target the needs to improve stroke patient management. The purposes are to identify the post-stroke life pathways components associated with sequelae (activity limitations - main purpose, cognitive disorders, anxio-depressive disorders, fatigue, participation restrictions) at 3 months and 1 year post-stroke, to define a typology of life pathways of patients during the post-stroke year and to analyze the social and geographical inequalities in the management of stroke. Methods Design: a prospective multicenter comparative cohort study with a follow up to 1 year after the acute episode. Participant centers: 13 hospitals in the Aquitaine region (France). Study population: patients diagnosed with a confirmed ischemic or hemorrhagic stroke included in the Aquitaine Observatory of Stroke (ObA2) cohort and voluntary to participate. Data sources are existing databases (ObA2 database and the French National Health Data System - SNDS) to collect information about care pathways, patient characteristics and stroke characteristics and Ad hoc surveys to collect information about life pathways and post-stroke sequelae. The endpoints of the study are post-stroke activity limitations evaluated by the modified Rankin score, other post-stroke sequelae (Cognitive disorders, anxio-depressive disorders, fatigue, restriction of participation) assessed by standardized and validated scales and Clusters of patients responding to pathways with common or similar characteristics.; Discussion By integrating a longitudinal dimension and relying on a large cohort, the project will make it possible to identify the sources of disturbances and the factors favorable to the outcome of the life pathways, important for the planning of the offer and the management of the public policies concerning stroke pathways. Trial registration ClinicalTrials.gov ID: NCT03865173, March 6th, 2019.